Comparison of Enzyme and Growth Characteristics in ALS-Inhibitor Susceptible and Resistant Annual Bluegrass (Poa annua) Biotypes. Issue 1 (March 2015) - Cross, Robert B.; McCarty, Lambert B.; McElroy, J. Scott; Tharayil, Nishanth; Bridges, William C.
Abstract : Acetolactate synthase–- (ALS-) inhibiting herbicides are frequently used to control annual bluegrass in managed turfgrass systems. Recently, the number of annual bluegrass populations resistant to these herbicides has increased on golf courses. Previous research involving annual bluegrass resistance to ALS inhibitors has included elucidating the mechanism of resistance and in vivo response of ALS to ALS-inhibiting herbicides. The purpose of this research was to generate baseline information on enzymatic parameters of resistant (R) and susceptible (S) annual bluegrass biotypes and further distinguish these biotypes by comparing vegetative growth and reproductive characteristics. The R biotype contained a mutation in the ALS gene resulting in a Trp 574 to Leu amino acid substitution. Compared to the S biotype, the R biotype exhibited a 27- and 10-fold resistance to trifloxysulfuron at the whole-plant level and under in vitro conditions, respectively. No significant differences were observed in substrate concentration at one-half maximum rate of enzyme activity (pyruvate) or extractable ALS activity between biotypes, but the maximum rate of enzyme activity was higher for the R biotype. The feedback inhibition of ALS activity by the branched-chain amino acids was higher for the R biotype than the S biotype, with leucine, valine, and isoleucine inhibiting ALS activity 20, 6, and 4% more in the R biotype, respectively. The R biotype produced more inflorescences and seeds per plant in comparison with the S biotype, but relative growth rates between biotypes were similar at all harvest intervals. Our research provides baseline information regarding ALS enzyme response, vegetative growth, and reproductive characteristics of annual bluegrass biotypes resistant and susceptible to ALS-inhibiting herbicides.